2017
DOI: 10.1002/mgg3.297
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation spectrum in ATP7B gene identified in Latvian patients with Wilson disease

Abstract: BackgroundWilson disease (WD) is an autosomal recessive disorder of copper metabolism caused by allelic variants in ATP7B gene. More than 500 distinct variants have been reported, the most common WD causing allelic variant in the patients from Central, Eastern, and Northern Europe is H1069Q.MethodsAll Latvian patients with clinically confirmed WD were screened for the most common mutation p.H1069Q by PCR Bi‐PASA method. Direct DNA sequencing of gene ATP7B (all 21 exons) was performed for the patients with WD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…However, in Korea, where WD is one of the most common inherited metabolic disorders, the carrier frequency and incidence of WD are estimated to be 1 in 88.2 and 1 in 30,778, respectively [ 4 ]. In Latvia, the estimated prevalence of WD is 1 in 24,000 cases [ 5 ]. Screening of WD in the UK population suggests that the frequency of individuals predicted to carry two mutant pathogenic ATP alleles is 1 in 7026, which is considerably higher than the typically reported prevalence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in Korea, where WD is one of the most common inherited metabolic disorders, the carrier frequency and incidence of WD are estimated to be 1 in 88.2 and 1 in 30,778, respectively [ 4 ]. In Latvia, the estimated prevalence of WD is 1 in 24,000 cases [ 5 ]. Screening of WD in the UK population suggests that the frequency of individuals predicted to carry two mutant pathogenic ATP alleles is 1 in 7026, which is considerably higher than the typically reported prevalence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, not all of the WD cases were confirmed molecularly [15]. One explanation of undiagnosed WD in a molecular level could be the fact that possibly WD patients with clinically confirmed WD diagnosis actually might have Wilson's disease-like disease.…”
Section: Discussionmentioning
confidence: 78%
“…Direct DNA sequencing of the ATP7B gene (promoter, exons and exon-intron boundaries) was performed for the patients with WD symptoms, being either heterozygous for H1069Q or without it on any allele. Methods for WD molecular confirmation and the group of WD patients have been described before in detail [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…The clinical manifestations of this mutation primarily involve extrahepatic symptoms such as tremor, dystonia, and mental symptoms. [ 13 ] In Asian populations, the most common mutation type is the Arg778Leu missense mutation in exon 8, which is most prevalent in China, South Korea, and Japan, with an allele frequency of 17.3% to 60%. The clinical symptoms associated with this mutation are predominantly liver damage, such as liver dysfunction and liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%